2022
DOI: 10.1002/ente.202201037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Electrolyte Concentration on the Nature of the Solid Electrolyte Interphase of a Lithium Metal Electrode

Abstract: The need of more powerful systems with higher energy density raises a lot of interest in lithium metal batteries (LMBs). As LMBs suffer from safety concerns due to the dendrite growth, several strategies have been studied to limit this growth. Using a highly concentrated electrolyte allows a homogeneous lithium plating that delays the formation of dendrites. Herein, different techniques are used in order to better understand the beneficial role of the salt concentration in the lithium plating/stripping. Operan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…According to the reference, it is reported that the NO 3 – anion enhances the ion–dipole interaction between Li + –DME, which conversely leads to weakening of Li + –anion (FSI – ) interactions . The enhanced interaction between Li + –DME can be confirmed by the stretching vibration peak of the DME solvent (C–O–C) in the Raman spectrum . Considering that the blue shift of the DME peak means a stronger Li + –DME interaction, the largest blue shift in BE-N (Figure S7) compared to BE reveals the strengthened ion–dipole interaction of the Li ion with the DME solvent.…”
Section: Resultssupporting
confidence: 76%
“…According to the reference, it is reported that the NO 3 – anion enhances the ion–dipole interaction between Li + –DME, which conversely leads to weakening of Li + –anion (FSI – ) interactions . The enhanced interaction between Li + –DME can be confirmed by the stretching vibration peak of the DME solvent (C–O–C) in the Raman spectrum . Considering that the blue shift of the DME peak means a stronger Li + –DME interaction, the largest blue shift in BE-N (Figure S7) compared to BE reveals the strengthened ion–dipole interaction of the Li ion with the DME solvent.…”
Section: Resultssupporting
confidence: 76%
“…Low reactivity was observed between the solvent molecules and Li‐metal electrode in electrolytes with a high salt concentration owing to the presence of inorganic SEI species formed by the decomposition of salt. [ 19 , 20 , 21 , 22 , 23 , 24 ] Additionally, localized highly concentrated electrolytes (LHCEs), which are achieved by incorporating fluorinated solvents into highly concentrated electrolytes (HCEs), overcome the intrinsic limitations of HCEs such as high viscosity and poor wettability. [ 25 , 26 , 27 , 28 ] LHCEs increase the proportion of cation‐anion aggregate species in the solvation structure of the electrolyte and aid in the construction of an anion‐driven SEI on the Li‐metal anode (Figure S1 , Supporting Information).…”
Section: Introductionmentioning
confidence: 99%